Body perception disturbances in women with pregnancy-related lumbopelvic pain and their role in the persistence of pain postpartum - Nina Goossens; Inge Geraerts; Lizelotte Vandenplas; Zahra Van Veldhoven; Anne Asnong; Lotte Janssens (BMC, 2021)
Abstract Background Lumbopelvic pain (LPP) is common during pregnancy and can have long-lasting negative consequences in terms of disability and reduced quality of life. Therefore, it is crucial to identify women at risk of having pregnancy-related LPP after childbirth. This study aimed to investigate the association between body perception, pain intensity, and disability in women with pregnancy-related LPP during late pregnancy and postpartum, and to study whether a disturbed body perception during late pregnancy predicted having postpartum LPP. Methods A prospective cohort study in 130 primiparous women (median age = 30 years) was performed. Pain intensity, disability, and lumbopelvic body perception during the last month of pregnancy and 6 weeks postpartum were assessed with the Numerical Pain Rating Scale (NPRS), Oswestry Disability Index, and Fremantle Back Awareness Questionnaire, respectively. Having pregnancy-related LPP was defined as an NPRS score ≥ 1/10. At both timepoints, women were categorized into three groups; pain-free, LPP with low disability, and LPP with high disability (based on Oswestry Disability Index scores). At each timepoint, body perception was compared between groups, and correlations between body perception, pain intensity, and disability were evaluated in women with LPP by using non-parametric tests. Logistic regression analysis was used to determine whether body perception during the last month of pregnancy predicted the presence of LPP 6 weeks postpartum. Results Women with LPP at the end of pregnancy, and 6 weeks postpartum reported a more disturbed body perception compared to pain-free women (p ≤ 0.005). Greater body perception disturbance correlated with higher pain intensity (σ = 0.266, p = 0.008) and disability (σ = 0.472, p < 0.001) during late pregnancy, and with pain intensity 6 weeks postpartum (σ = 0.403, p = 0.015). A disturbed body perception during late pregnancy nearly significantly predicted having postpartum LPP (Odds Ratio = 1.231, p = 0.052). Conclusions Body perception disturbance was greater in women experiencing LPP during late pregnancy and postpartum compared to pain-free women, and correlated with pain intensity and disability. Though non-significant (p = 0.052), the results of the regression analysis suggest that greater body perception disturbance during late pregnancy might predict having LPP postpartum. However, future studies should follow up on this.